Risk of Pleural Empyema in Adult Patients With Asthma: A Nationwide Retrospective Cohort Study - Liao, Wei-Chih; Lin, Cheng-Li; Shen, Te-Chun; Tu, Chih-Yen; Hsia, Te-Chun; Hsu, Wu-Huei (Frontiers in Medicine, 2022)
Background Respiratory system infections commonly occur among individuals with asthma. However, whether asthma patients have a higher risk of pleural empyema development remains unclear. Methods This is a retrospective cohort study based on data from the National Health Insurance Research Database of Taiwan. The asthma cohort consisted of 48,360 newly diagnosed adult individuals from 2000 to 2012. The comparison cohort consisted of the same number of adults who did not have asthma and was matched for age, gender, comorbidity, and the year of diagnosis. The development of pleural empyema was followed up to 2013. Results Pleural empyema incidence was 2.03-fold higher in the asthma cohort compared to the comparison cohort (8.65 vs. 4.25 per 10,000 person-years), with an adjusted hazard ratio (HR) of 2.12 [95% confidence interval (CI) = 1.76–2.56]. Stratified analyses by age, gender, comorbidity, and corticosteroid use revealed that the crude and adjusted HRs of pleural empyema associated with asthma were all significant. Among patients with asthma, the risk of pleural empyema elevated with increased frequency of annual asthma-related emergency room visits and hospital admissions (≥1 vs. <1, aHR = 8.07, 95% CI = 4.31–15.1 and aHR = 9.31, 95% CI = 5.56–15.6). Conclusion An increased risk of pleural empyema occurrence was observed in adult patients with asthma than those without asthma. Furthermore, the risk of pleural empyema may increase with poor control of asthma.